Immune Co-inhibitory Receptors PD-1, CTLA-4, TIM-3, LAG-3, and TIGIT in Medullary Thyroid Cancers: A Large Cohort Study - Shi, Xiao; Li, Cui-Wei; Tan, Li-Cheng; Wen, Shi-Shuai; Liao, Tian; Zhang, Yan; Chen, Tong-Zhen; Ma, Ben; Yu, Peng-Cheng; Lu, Zhong-Wu; Qu, Ning; Wang, Yu; et al. (The journal of clinical endocrinology and metabolism, 2021)
Abstract Context Programmed cell death protein-1 (PD-1), cytotoxic T-lymphocyte antigen 4 (CTLA-4), T-cell immunoglobulin and mucin-domain containing-3 (TIM-3), lymphocyte activation gene-3 (LAG-3), and T-cell immunoglobulin and ITIM domain (TIGIT) are considered major immune co-inhibitory receptors (CIRs) and the most promising immunotherapeutic targets in cancer treatment, but they are largely unexplored in medullary thyroid carcinoma (MTC). Objective We aimed to provide the first evidence regarding the expression profiles and clinical significance of CIRs in a large cohort of MTC patients. Design and Patients In total, 200 MTC patients who received initial surgery in our hospital were included. Immunohistochemistry was performed to evaluate CIR expressions in tissue microarrays (TMAs). Combined with the results of our previous programmed cell death ligand-1 (PD-L1) study, clinicopathologic and prognostic correlations of these proteins were retrospectively analyzed. Results TIM-3, PD-1, CTLA-4, LAG-3, and TIGIT positivity was detected in 96 (48.0%), 27 (13.5%), 25 (12.5%), 6 (3.0%), and 6 (3.0%) patients, respectively, in whom TIM-3, PD-1, and CTLA-4 expressions were positively correlated. Log-rank tests and multivariate Cox analyses both indicated that TIM-3, CTLA-4 expression, and PD-1/PD-L1 coexpression were associated with worse structural recurrence-free survival. In addition, among 20 patients who developed advanced disease during follow-up, 12 (60%) showed TIM-3 positivity, among whom 6 cases also had concurrent moderate to strong PD-1, PD-L1, or CTLA-4 expression. Conclusions Using the currently largest TMA cohort of this rare cancer, we delineated the CIR expression profiles in MTC, and identified TIM-3, CTLA-4 expression, and PD-1/PD-L1 coexpression as promising biomarkers for tumor recurrence. Furthermore, a subset of advanced MTCs are probably immunogenic, for which single or combined immunotherapy including TIM-3, PD-1, PD-L1, or CTLA-4 blockade may be potential therapeutic approaches in the future.